A FAMILY RESILIENCE IN EARLY MARRIAGE COUPLES IN DUKUH MENCEK VILLAGE, SUKORAMBI SUB-DISTRICT: FAMILY RESILIENCE IN EARLY MARRIAGE COUPLES IN DUKUH MENCEK VILLAGE, SUKORAMBI SUB-DISTRICT - Faridatus Sholihah; Achmad Fathor Rosyid (Jurnal Penelitian Multidisiplin, 2023)
Family resilience describes a harmonious and prosperous relationship both physically and spiritually. This study raises the issue of how family resilience in early marriage couples and what are the factors that influence family resilience in early marriage couples in Dukuh Mencek Village, Sukorambi District, Jember Regency. The purpose of this study was to describe family resilience in early marriage couples and describe the factors that influence family resilience in early marriage couples in Dukuh Mencek Village, Sukorambi District, Jember Regency. This study uses a descriptive qualitative approach. The results of this study indicate that family resilience in early marriage couples in Dukuh Mencek Village is seen from three aspects. First, the physical aspect, namely early married couples meet their needs by gardening and working odd jobs so that their clothing and food needs are met. Second, the psychological aspect by looking at the ability to calm down in solving problems. Third, the factor of social resilience is the ability to interact well within the community, to be able to accept suggestions and input from the environment.